Barriers and facilitators to detection and treatment of obstructive sleep apnoea syndrome in people with severe mental illnesses, qualitative interview study and referrer survey - Sophie Faulkner; Joseph Firth; David Shiers; Megan Kalucy (BMC Psychiatry)
Abstract Obstructive sleep apnoea syndrome (OSAS) is a relatively common condition. It has a range of negative health and quality of life implications, but there are established tests to detect it, and recommended treatment pathways which have been well tested. OSAS is prevalent in people with severe mental illness (SMI), and research suggests it is under-detected in this group. This study aimed to examine and explore barriers and facilitators to the detection and treatment of OSAS in people with severe mental illnesses. Staff and patients with a range of relevant experiences were interviewed, and a large scale survey of potential OSAS referrers was conducted. Interviews were analysed thematically, survey responses were summarised descriptively, and results are presented together for comparison and enhanced interpretation. The results highlight a lack of awareness of OSAS outside of specialist sleep services, resulting in poor detection and treatment of OSAS in people with SMI. Comorbidities, symptoms and circumstances of this group may make the presence of OSAS less obvious, and can make diagnosis and adapting to treatment more difficult, but also emphasise the benefits of successful continuous positive airway pressure (CPAP) treatment in this group. The challenges of adapting to CPAP were described and acknowledged, but the impact of successful CPAP was for some life changing. The harm of delayed diagnosis was perceived as unjust. We recommend increased screening for OSAS in people with SMI, supported by increased education and training about OSAS in staff who work with people with severe mental illnesses, and increased awareness in service users and carers.